The Impact of Globalization on Human Smuggling and Economic Policy Responses - Zulyadi, Rizkan; Pinem, Serimin; Nasution, Sulhan Iqbal; Meher, Montayana; Ramadhan, Muhammad Citra (Unissula, 2025)
Globalization has created an interconnected and interdependent world, brought various conveniences while simultaneously raised new challenges in human rights issues. One prominent negative impact is the rise of Transnational Organized Crime (TOC), including human smuggling, which is increasingly facilitated by technological developments and market openness. This practice resembles a free market, where actors compete to attract customers without formal mechanisms for resolving disputes or enforcing contracts, giving rise to trust issues that are often addressed through reputational investment. This study aims to examine the gaps in Indonesia's national law in responding to this phenomenon and assess its relevance to international standards, particularly the Palermo Protocol. Using normative methods through literature review and a comparative approach, this study highlights the relationship between globalization, human smuggling, and the existing legal framework. The findings indicate that although the UN, through the UNODC and the Conference of Parties (COP), has initiated TOC prevention mechanisms, their implementation remains weak without strong normative ties. In conclusion, harmonization of Indonesian law with international standards is needed to strengthen human rights protection and the effectiveness of law enforcement against human smuggling.